Comparative study of new MPPT control approaches for a photovoltaic system - Haddou, Ahmed; Tariba, Nour-Eddine; Ikken, Naima; Bouknadel, Abdelhadi; EL Omari, Hafsa; El Omari, Hamid (Institute of Advanced Engineering and Science, 2020)
The output characteristics of the photovoltaic (PV) installation normally depend on solar radiation and ambient temperature, the charge impedance, its maximum power point (MPP) is not constant. In each state of the PV module has a point where it can produce its MPP. Therefore, MPPT (Maximum Power Point Tracking) methods can be used to keep the photovoltaic panel running on its MPP. In this article, the objective was to determine how the different maximum point power monitoring (MPPT) techniques applied to PV systems work. Therefore, two MPPT algorithms are presented and compared under different temperature and radiation conditions: MRAC methods and sliding mode controller combined with the Incremental Conductivity (IC) algorithm. These algorithms are widely used in PV systems because of their easy implementation and low cost. These techniques were analyzed and their performance evaluated using the PSIM software under different types of solar radiation and temperature.